Revision of the Nearctic Calliphora Robineau-Desvoidy (Diptera: Calliphoridae) - Tantawi, Tarek I.; Whitworth, Terry L.; Sinclair, Bradley J. (Zootaxa, 2017)
The Nearctic species of Calliphora Robineau-Desvoidy are revised and all species are redescribed and/or diagnosed. Diagnostic characters to permit reliable identification of both sexes of Calliphora aldrichia (Shannon) and C. montana (Shannon) and detailed distributional records for both species are provided for the first time. A lectotype is designated for Calliphora loewi Enderlein, 1903. A revised key to the 13 species of Nearctic Calliphora is also included. The key is based on examination of over 1,000 specimens from across North America and the structure of the terminalia of both sexes of each species. Complete illustrations of the terminalia of both sexes are provided for all species, including those of eight poorly known species: Calliphora alaskensis (Shannon), C. aldrichia (Shannon), C. coloradensis Hough, C. grahami Aldrich, C. latifrons Hough, C. livida Hall, C. montana (Shannon) and C. terraenovae Macquart. The female terminalia of C. alaskensis, C. aldrichia, C. coloradensis, C. livida and C. montana are illustrated for the first time. Barcode data for all 13 species of Nearctic Calliphora are provided, several for the first time. Results support current species concepts but barcodes failed to distinguish C. aldrichia and C. montana.